Through the Looking Glass: An Analysis of the Portrayals of Child Soldiers through the Lenses of Community Members and Key Stakeholders - Arici, Claudia (2020)
This thesis explores the construction and deployment of global representations of child soldiers. The main argument is that understanding the representation of child soldiers by unravelling the way it is constructed has an important impact on policy applications when addressing child soldiers. In broadening the theoretical, conceptual and practical interpretations of the concept of ‘child soldier’, this thesis demonstrates some of the political effects of these portrayals. Given the multidimensional and multifaceted nature of the child soldier phenomenon, a cross-disciplinary approach is employed. Considering the relationship context in which child soldiers exist, this thesis argues that the child soldiers’ identity is a complex one that cannot be considered in isolation from the external stakeholders who contribute to its creation. Nor can the representation of child soldiers be dissociated from environmental, structural and cultural factors. Politically and materially, the identity ‘child soldier’ carries a range of meanings and implications in the process of post-war rehabilitation and reintegration of child ex-combatants into society. In these contexts, new meanings of childhood and of youth as a political identity emerge — meanings influenced by international discourse around children’s rights. The main hypothesis of my thesis is that the representation of child soldiers cannot escape the institutional, political and social positioning of the stakeholders. It is not possible to represent or act from the ‘outside’, since everyone is always already situated inside discourse, culture, institutions and geopolitics. Consequently, portrayals are always mediated by a confluence of diverse institutional interests and other identifiable externalities; in this regard, representation serves a utilitarian purpose